Firm financing and the relative demand for labor and capital - Khalid ElFayoumi (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
During both the 2008 and the COVID crises, aggregate employment in Europe and the US fell despite continuing growth in the aggregate capital stock. Using more than one million firm-year observations of small and medium European firms between 2003 and 2018, this paper introduces new stylized facts on how firms' relative demand for labor and capital evolved as their capital structure adjusted to the events of the 2008 crisis. It also provides the first micro-level evidence that firms substitute capital for labor when financing costs rise. The empirical evidence lends support to the hypothesis that substitution is driven by an incentive to raise holdings of collateralizable capital. The analysis uses the heterogeneous effects of ECB monetary policy surprises across the firm distribution to identify exogenous firm-level external financing shocks. The results suggest that maintaining a well functioning credit market supports a higher labor share of economic growth.
Keywords: E3; E5; G3; J2; J3; 330; labor demand; financial frictions; jobless growth; labor share